Probing the Higgs-Gauge Couplings at Leptonic Colliders (Письма в ЭЧАЯ, 2024)
In this work, we investigate the Higgs-gauge couplings $hVV$ (with $V=W,Z$) through different final states at leptonic colliders. In many SM extensions, these couplings could be modified as $g_{hVV}=\kappa_{V}g_{hVV}^{SM}$, either via radiative contributions or due compositeness nature of the Higgs and/or gauge bosons. As a first step, by assuming that theHiggs-gauge couplings are SM-like ($\kappa_{V}=\pm1$), we consider the three final states at leptonic colliders $h u\bar{ u}\,@\,250\,\mathrm{GeV}$,$hW^{+}W^{-}\,@\,500\,\mathrm{GeV}$ and $ZW^{+}W^{-}\,@\,1\,\mathrm{TeV}$(with $h\rightarrow b\bar{b}$,~$Z\rightarrow jj$ and $W^{-}\rightarrow\ell^{-}\bar{ u}$); in order to identify $\kappa_{V}$ sings via possible deviation of the cross section values with respect to the SM. Then, by considering that such a deviation in $\kappa_{V}$ with respect to the SM can not be seen at HL-LHC, i.e., $\left|\delta\kappa_{V}/\kappa_{V}\right|\approx0.04\sim0.05$, we explore these three processes in the signal case $\left|\kappa_{V}\right|=1$ to produce some kinematic variables distributions. This may affectthe cross section and the kinematic distributions, and tiny excess or lack in events could be reported.